Employment Effects of Army Service and Veterans' Compensation: Evidence from the Australian Vietnam-Era Conscription Lotteries - Siminski, Peter (The Review of Economics and Statistics, 2013)
Exploiting Australia's National Service lotteries of 1965 to 1972, I estimate the effect of army service on employment outcomes. Population data from military personnel records, tax returns, veterans' compensation records, and the Census facilitate a rich and precise analysis, identified by 53,000 complying conscripts. The estimated employment effect is −12 percentage points (95% CI: −13, −11) overall, −37 for those who served in Vietnam and 0 for those who served only in Australia. It emerged in the 1990s, mirrored by veterans' disability pension effects. These results contrast with those for the United States, possibly reflecting employment disincentives associated with Australia's veterans' compensation system.